Media Pembelajaran Sistem Kendali Pensaklaran Jarak Jauh berbasis IoT di Prodi S1 Pendidikan Teknik Elektro Undiksha - Gede Yogi Adhi Parawansa; I Gede Ratnaya; I Gede Made Surya Bumi Pracasitaram (Universitas Pendidikan Ganesha, 2022)
This study aims to create an IOT-Based Remote Switching Control System Learning Media in the Undiksha Electrical Engineering Education Undergraduate Study Program. Knowing the feasibility of the Iot-Based Remote Switching Control System Learning Media, and knowing the responses of students or students to this learning media. This research is classified as R&D (Research and Development) research. This study uses a statistical analysis method used to process percentages of content experts, media experts, and field trials. This study used a questionnaire as an instrument for collecting data from content experts, media experts, and students. The research results obtained: the results of the media expert test got a percentage of 98.33% with very decent qualifications, and the content expert validation test got a percentage of 96.36% with very decent qualifications. The score range for all 6 small group test respondents is listed in very high qualification, and the score range for 20 large group test respondents is all listed in very high qualification. IOT-Based Remote Switching Control System Learning Media in Undiksha's Undergraduate Electrical Engineering Education Study Program is suitable for use in the learning process.